Detection by LIBS of the deuterium retained in the FTU toroidal limiter. (January 2019) - Maddaluno, G.; Almaviva, S.; Caneve, L.; Colao, F.; Lazic, V.; Laguardia, L.; Gasior, P.; Kubkowska, M.
Highlights: Laser Induced Breakdown Spectroscopy: a suitable tool to measure gas retention. Deuterium (D) retained in the FTU toroidal limiter tiles was detected from remote. Good resolution of Dα and Hα spectral lines under vacuum conditions. D detected in the boron layer deposited by glow-discharge with Deuterated Diborane. Abstract: In this paper the Laser Induced Breakdown Spectroscopy (LIBS) measurement of the deuterium (used as a proxy for tritium) retained in and the surface elemental composition of the FTU Mo (TZM) toroidal limiter tiles, carried out from remote (∼2.5 m) during short breaks of the operations or during machine maintenance, are reported. Single pulse technique has been used with the FTU vessel under high vacuum or in Nitrogen or Argon atmosphere. In vacuum experiments Dα and Hα lines have been detected with good resolution, while in Ar atmosphere (5 × 10 4  Pa) the two lines were partially overlapped due to Stark broadening. First results of measurements in N2 atmosphere (10 5  Pa) showed no presence of Dα and Hα lines. These measurements were also carried out for supporting the foreseen use of a robotic arm for an extended LIBS analysis of retained deuterium in the FTU vessel components.